SISTEM INFORMASI TRACER STUDY ALUMNI PROGRAM STUDI D-III MANAJEMEN INFORMATIKA DAN KOMPUTERSASI AKUNTANSI UNIVERSITAS METHODIST INDONESIA - Robert Simangunsong; Roni Jhonson Simamora; Resianta Perangin-angin (Universitas Methodist Indonesia, 2021)
Tracer Study or alumni tracking is one of the methods used by several universities in Indonesia, to obtain input and feedback from alumni. Input and feedback obtained from alumni can be an improvement and development of the quality of the education system implemented at the university. Tracer studies are also useful in providing important information about the relationship between institutions and the world of work. The Tracer Study of the Indonesian Methodist University is still using a form (Paper Based), one of which is the D-III study program of Informatics Management and Computerized Accounting. The D-III study programs from previous years have produced many alumni who are ready to work, alumni data and the management system have not been saved to the database, so the stored data can be damaged, lost and it will take time to find alumni data. Therefore, a web-based tracer study information system is needed so that the system can be computerized. The website is built using the HTML, PHP, Bootstrap and MYSQL programming languages ​​as a data storage system or commonly called a database. The existence of this alumni tracer study website can facilitate the process of implementing the alumni tracer study. The system built is expected to improve and develop the quality of the current system.